Group Guidance Services with Self-Management Techniques to Reduce Students' Verbal Aggressive Behavior - Neviyarni S; Novita, Rita (Department of Guidance and Counseling, FIP, Undiksha, 2022)
The increase in students' verbal aggressive behavior every year must be eliminated or reduced in order to have a positive impact. One of the efforts made to reduce students' verbal aggressive behavior at school is to carry out group guidance services with self-management techniques. This study aims to describe the differences in student aggressive behavior with the experimental group guidance service using self-management techniques and the control group guidance service without using self-management techniques. This study uses a Quasi Experiment with The Non Equivalent Control Group design. The results showed that there was a significant difference in the aggressive behavior of experimental group students who were given group guidance services using self-management techniques with control group students who were given group guidance services without using self-management techniques; this can be seen in the average posttest score of the experimental group dropped higher than the average posttest score of the control group. Thus, group guidance services use self-management techniques effectively to reduce students' verbal aggressive behavior.